Synthesis of main group and transition metal complexes with the (8-quinolyl)cyclopentadienyl ligand and their application in the polymerization of ethylene - Enders, Markus; Kohl, Gerald; Pritzkow, Hans (Organometallics, 2004)
Nucleophilic addition of 8-lithioquinoline to the Cp2Co+ cation leads to the formation of η4-(8-quinolylcyclopentadiene)(η5-cyclopentadienyl)cobalt(I) (7). Oxidative decomplexation with FeCl3 liberates the quinolyl-substituted cyclopentadiene derivative 2a, which is stable at low temperature only. Deprotonation by strong bases such as NaH or KH leads to the alkali metal quinolyl cyclopentadienide salts, which are used as precursors for the synthesis of the corresponding Ti, Cr, and Al complexes. Whereas after its activation the aluminum compound 13 does not yield an olefin polymerization catalyst, the chromium(III) complex 12 reacts with methylaluminoxane (MAO) to give a highly active catalyst for the polymerization of ethylene.